Algunas consideraciones sobre la mediación y arbitraje - Mendoza Córdova, Karen Tatiana; Ochoa Espinoza, Amanda Magdaly (Machala, 2019)
A descriptive investigation of a bibliographic review type was carried outwith the objective of showing some considerations about mediation and arbitration. On this basis, the methodological strategy was systematized through general research methods such as the historical-logical, the hermeneutic, the documentary analysis and the synthetic-analytic. In addition, the use of content analysis technique. In this sense, a theoretical systematization related to the subject was carried out. The foregoing allowed to deepen in some aspects related to the subject such as: the alternative methods of resolution of conflicts and national and international controversies endorsed by the Constitution of the Republic and the legislative system that regulates the process and execution. Also, to detect the existence of some insufficiency such as: insecurity in the confidentiality of the information when being transferred by the telematic route and existence of arbitration agreements, in commercial contracts, truly pathological. However, it can be asserted that the subject is an important aspect in the business world
Se realizó una investigación descriptiva de tipo revisión bibliográfica con el objetivo de mostrar algunas consideraciones sobre la mediación y el arbitraje. Sobre esta base,la estrategia metodológica se sistematizó a través de métodos generales de investigacióncomo el histórico-lógico, el hermenéutico, elanálisis documental yel analítico–sintético. Además, del empleo dela técnica deanálisis de contenido. En este sentido, se realizó una sistematización teórica relacionada conlatemática. Lo anterior,permitióprofundizar en algunos aspectos relacionados con la temática como son:losmétodos alternos de resolución de confictos y controversia nacionales e internacionales avalados por la Constitución de la República y elsistema legislativo que norma eltrámite y ejecución. Asimismo, detectar la existenciaalgunas insuficienciacomo: inseguridad en la confidencialidad de la información al ser transferidapor la vía telemática y existencia de convenios arbitrales,en los contratos comerciales,verdaderamente patológicos. No obstante, se puede aseverar que la temática constituye un aspecto importante en el mundo de los negocios.
Keywords: ARBITRAJE INTERNACIONAL; RESOLUCION DE CONFLICTO; APREMIO PERSONAL